Nicaragua : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2005)
Nicaragua's report on the Observance of Standards and Codes examines Data Module, response by the authorities, and detailed assessments using the data quality assessment framework. The Ministry of Finance and Public Credit provides an institutional environment for compiling budgetary transactions data but not for compiling statistics for general government and/or nonfinancial public enterprises. The environment fosters good arrangements for data sharing among agencies involved in government finance statistics compilation and dissemination.